Analysis of Quantum Physics Lectures from the Perspective of the MBKM and OBE Based Higher Education Curriculum - Irvani, Asep Irvan; Rochintaniawati, Diana; Riandi, Riandi; Sinaga, Parlindungan; Henukh, Anderias (Department of Physics Education, Universitas Mataram, 2024)
Lecture analysis in the core courses of the study program contributes to the evaluation of the curriculum used. This field study was carried out to analyze Quantum Physics lectures from the perspective of a university curriculum based on Independent Learning Campus (MBKM) and Outcome-Based Education (OBE). Data collection techniques were carried out through observing the implementation of learning in the Quantum Physics course, interviews with lecturers teaching quantum physics courses, and reviewing curriculum tools in the form of curriculum books, semester lecture plans (RPS), and assessment documents. The instruments used refer to content standards, process standards and learning assessment standards listed in Permendikbud Number 3 of 2020, Permendikbudristek Number 56 of 2022, and Permendikbudristek Number 53 of 2023. The participants involved in this research were a lecturer and 29 students of the undergraduate physics education study program at one of the universities in Garut Regency. The lecturer in question is a lecturer who teaches quantum physics courses, while the students in question are final year students who are taking quantum physics courses in the odd semester of the 2023/2024 academic year. Data collection was carried out over the period October – November 2024. Data analysis was carried out qualitatively using a data triangulation approach. The results of data analysis show that in the Bachelor of Physics Education curriculum, the Quantum Physics course is in the group of upper-level compulsory courses with physics concept study material. From an MBKM perspective, this course can be converted to Program Pertukaran Mahasiswa (PMM) and Program Magang dan Studi Independen Bersertifikat (MSIB), but cannot be converted to the Teaching Campus Program. Conversion to the PMM program is carried out by taking courses in other study programs that have course learning outcomes that are related to quantum physics. Conversions to the MSIB program are carried out at companies or agencies related to the application of quantum physics concepts. From an OBE perspective, this course contributes to graduate learning outcomes in Specific Skills and supports the graduate's profile as a Physics Teacher. The special skill in question is being able to apply mathematical models in explaining physical phenomena in learning.